Duration of export relationships of Philippine MSMEs - Mark Edison Bautista; George Manzano (Philippine Institute for Development Studies (PIDS), 2018)
Within the framework of the Asia-Pacific Economic Cooperation (APEC) Boracay Action Agenda and the ASEAN Strategic Action Plan developed by its members to assist micro, small, and medium enterprises (MSMEs) to reach internationalization, the study examines the survivability of Philippines MSMEs' exports to select countries. The analysis is based on the survival analysis model of Besede and Prusa (2006a; 2006b) and Besede and Prusa (2008). Using the Kaplan Meier estimator model in both the MSME exports and the total trade data in documenting the survival rate of goods and duration of Philippine exported products, the study finds that most export relationships of the Philippines are brief, contrary to conventional trade theories which suggest that most trade relationships will be long-lived. Also, MSMEs, on average, account for a more significant number of export relations than large establishments. Furthermore, among MSMEs, it is the medium-sized firms that constitute the majority of export relations over different durations.
Keywords: 330; survival analysis; duration; export survival; MSMEs